DAMPAK PENGUMUMAN PERINGKAT OBLIGASI PADA KINERJA OBLIGASI DI BURSA EFEK INDONESIA - Yuharningsih Yuharningsih; ST. Haryono ST. Haryono (University of Merdeka Malang, 2015)
The purpose of this study was to determine empirically the changes on bond rating that impacted on the bond’s performance. The changes on bond rating were rated by PT Pefindo. This study used 65 samples from 30 companies with bonds data issued in 2009 – 2012. The samples were grouped into 13 upgrade bonds, 8 downgrade bonds and 44 stable. Bond’s performance was indicated by the value of yield to maturity (YTM). The paired t-test was deployed with software SPSS version 15. The result showed that there was no different performance before and after the announcement of bond ratings for both the entire sample and upgrade bond groups. While for downgrade groups there was a significant difference before and after the announcement of bond ratings. These result indicated that only downgade group had a significant difference from YTM, therefore bond ratings announcement contained useful information for the investors.